2012
DOI: 10.1007/s11745-012-3682-1
|View full text |Cite
|
Sign up to set email alerts
|

Partially Hydrolyzed Guar Gums Reduce Dietary Fatty Acid and Sterol Absorption in Guinea Pigs Independent of Viscosity

Abstract: This study investigated the effect of two partially hydrolyzed guar gums (PHGG) on fatty acid and sterol excretion. PHGG were obtained by chemical hydrolysis of guar gum (GG) with H(2)O:EtOH (1:1) at 100 °C for 1 h (PHGG1) or 2 h (PHGG2). The viscosity of the PHGG in a 1 % (w/v) aqueous solution corresponded to that of a pseudoplastic fluid and was higher for PHGG1 than PHGG2. Guinea pigs (n = 8 per group) were fed high fat diets (17/100 g) that contained 12/100 g of cellulose, PHGG1, or PHGG2 for 4 weeks. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Our results were in consistent with Ndou et al [38], in which both soluble ber ( axseed meal) and insoluble ber (oat hulls) decreased serum total cholesterol concentration in pigs, showing hypocholesterolemic effects. As a source of soluble ber, the SBP can increase digesta viscosity, and hence increase cholesterol and bile acid excretion, which may in turn in uence hepatic cholesterol metabolism, and eventually result in decreased serum cholesterol concentration [39]. While as a source of insoluble ber, the WB can increase cholesterol and bile acid excretion by shortening transit time of digesta in the gastrointestinal tract [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in consistent with Ndou et al [38], in which both soluble ber ( axseed meal) and insoluble ber (oat hulls) decreased serum total cholesterol concentration in pigs, showing hypocholesterolemic effects. As a source of soluble ber, the SBP can increase digesta viscosity, and hence increase cholesterol and bile acid excretion, which may in turn in uence hepatic cholesterol metabolism, and eventually result in decreased serum cholesterol concentration [39]. While as a source of insoluble ber, the WB can increase cholesterol and bile acid excretion by shortening transit time of digesta in the gastrointestinal tract [38].…”
Section: Discussionmentioning
confidence: 99%
“…A study in guinea pigs fed two kinds of partially hydrolysed guar gum (i.e. hydrolysed for either 1 or 2 h) showed that both types displayed cholesterol-lowering effects [ 27 ]. In the present study, we found differences between the guar gum preparations regarding blood levels of cholesterol and TG, possibly due to the fact that we had a wider range of viscosity (from 0.02 to 600 Pa ● s) than in the Santas et al study (ranging between 1.7 to 2.9 Pa ● s) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…hydrolysed for either 1 or 2 h) showed that both types displayed cholesterol-lowering effects [ 27 ]. In the present study, we found differences between the guar gum preparations regarding blood levels of cholesterol and TG, possibly due to the fact that we had a wider range of viscosity (from 0.02 to 600 Pa ● s) than in the Santas et al study (ranging between 1.7 to 2.9 Pa ● s) [ 27 ]. Of note, the lipid metabolism was distinctly affected by the viscosity of the guar gum, where low viscosity reduced blood cholesterol and TG levels, and high viscosity instead reduced liver steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this speculation is the increase in the presence of trans FA which are likely to be of microbial origin (Martínez Marín et al, 2013). Therefore, the presence of long-chain unsaturated FA in gastrointestinal contents can be used as reliable indicators to assess the effects of feeding DF and its fermentability on lipid metabolism (Santas et al, 2012). These findings also indicate that endogenous secretions of FA from the host into gastrointestinal contents might have contributed to the ileal and fecal flows of these FA.…”
Section: Discussionmentioning
confidence: 87%